2017
DOI: 10.1177/1535370217723628
|View full text |Cite
|
Sign up to set email alerts
|

Human skin gene expression: Natural (trans) resveratrol versus five resveratrol analogs for dermal applications

Abstract: Resveratrol (RV) is a polyphenolic compound naturally produced by plants. Polyphenolic compounds incorporated into medicinal products are beneficial but, RV is rapidly metabolized with an associated decline in biological activity. This study tested RV as the standard and compared five structurally modified RV analogs: butyrate, isobutyrate, palmitoate, acetate, and diacetate (to improve functionality) at 1% concentration(s) for 24 h in epiderm full thickness cultures by gene array/qPCR mRNA analysis. When sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(116 reference statements)
0
17
0
Order By: Relevance
“…Resveratrol significantly increased the production of antioxidants such as catalase and superoxide dismutase (SOD) as well as expression of SIRT1 and extracellular matrix (ECM) proteins such as collagen and elastin. In addition it significantly inhibited pro-inflammatory mediators (IL-1A, IL-6, IL-8) and biomarkers of skin aging, such as transforming growth factor beta 1 (TGFB1), transforming growth factor beta receptor 2 (TGFBR2), tumor necrosis factor receptor 1A (TNFRSF1) and S100 calcium-binding protein A8 (S100 A8) (Lephart and Andrus, 2017 ). The antioxidant property is an essential aspect of the protective effect of resveratrol.…”
Section: Grape Seed Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol significantly increased the production of antioxidants such as catalase and superoxide dismutase (SOD) as well as expression of SIRT1 and extracellular matrix (ECM) proteins such as collagen and elastin. In addition it significantly inhibited pro-inflammatory mediators (IL-1A, IL-6, IL-8) and biomarkers of skin aging, such as transforming growth factor beta 1 (TGFB1), transforming growth factor beta receptor 2 (TGFBR2), tumor necrosis factor receptor 1A (TNFRSF1) and S100 calcium-binding protein A8 (S100 A8) (Lephart and Andrus, 2017 ). The antioxidant property is an essential aspect of the protective effect of resveratrol.…”
Section: Grape Seed Polyphenolsmentioning
confidence: 99%
“…To improve its efficacy for cosmetic and medical applications, multiple studies have been conducted to develop resveratrol analogs that are more stable and more biologically active than the natural form. There is evidence that some of the analogs have great potential to be used for topical applications (Sirerol et al, 2015 ), especially considering that some were found to display increased potency and longer half-life compared to resveratrol (Lephart and Andrus, 2017 ). It is important that future studies determine how chemical modifications to resveratrol impact its beneficial effects in topical application and perhaps, even its bioavailability after oral ingestion.…”
Section: Grape Seed Polyphenolsmentioning
confidence: 99%
“…Both ethanol and DMSO are well-recognized transepidermal penetration enhancers for a variety of active principles in solution [ 9 , 10 , 45 ]. Since long-term application of organic solvents on the skin cannot be feasible in humans, vehicle formulations suitable for skin delivery of resveratrol [ 46 , 47 , 48 ] or quercetin [ 49 , 50 ], or chemical modifications facilitating their transcutaneous penetration [ 51 , 52 ] are under active development. Our data emphasize the potential effectiveness of resveratrol and quercetin in the prevention of type I IFN-driven pro-inflammatory circuits in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…However, as skin’s metabolism remains relevant, the use of RSV prodrugs for skin diseases or for aesthetic indications (e.g., anti-aging and skincare) could have some advantages. For these reasons, the interest in using RSV prodrugs for dermal applications has been growing significantly (Table 7) [156,157,158,159].…”
Section: Prodrugsmentioning
confidence: 99%